Cajal bodies and snRNPs - friends with benefits - Staněk, David (RNA biology, 2017)
Spliceosomal snRNPs are complex particles that proceed through a fascinating maturation pathway. Several steps of this pathway are closely linked to nuclear non-membrane structures called Cajal bodies. In this review, I summarize the last 20 y of research in this field. I primarily focus on snRNP biogenesis, specifically on the steps that involve Cajal bodies. I also evaluate the contribution of the Cajal body in snRNP quality control and discuss the role of snRNPs in Cajal body formation.
Keywords: Spliceosomes; Protein Binding; Transcription, Genetic; Coiled Bodies; posttranskripční úpravy RNA; genetická transkripce; spliceozomy; vazba proteinů; Cajalova tělíska; Animals; ribonukleoproteiny malé jaderné; lidé; Humans; RNA Processing, Post-Transcriptional; zvířata; Ribonucleoproteins, Small Nuclear